The Effect of Crude Extract of Pandanus conoideus Lamb. var. Yellow Fruit on Apoptotic Expression of the Breast Cancer Cell Line (T47D) (Biodiversitas Journal of Biological Diversity, 2008)
A mechanism controlling a growing cancer cells is by a programmed cell death (apoptosis). The wildtype-p53 enable to stop cleaves that follow DNA repair or cell death (apoptosis). The mutation of wt-p53 caused loosing its ability to inhibit cancer cells proliferation. Healing methods like surgery, radiation, immunotherapy and chemotherapy still have some weaknesses, and clinical medicine to cancer is also still has any dissatisfactory. Much of chemotherapy was not given optimal result yet, because no specific action to cancer cells only, but also to the normal cells. These problems encourage important effort to find specific and sensitive anticancer. Empirical evidence indicates that the crude extract of Pandanus conoideus Lamb var. yellow fruit has potential effect as an anticancer. Method of Freshney was used in growing T47D cell line, counting cells was done by direct counting, and apoptotic evaluation was done by TUNEL enzymatic labeling assay. The results of theresearch demonstrated that the LC50 of yellow fruit extract are 0.25 μL/mL. The percentage of apoptotic of 0.125 μL/mL,0.0625 μL/mL, and 0.03125 μL/mL are 34.38±2.26, 30.03±3.87 and 21.07±1.14 respectively.Key words: T47D, Apoptotic, p53, Pandanus conoideus Lamb. var. yellow fruit.